DIGITAL TOOLS UTILIZATION AND CHEMISTRY STUDENTS’ ACADEMIC ACHIEVEMENT IN THE TEACHING OF SOAP PRODUCTION IN SECONDARY SCHOOLS IN AKWA IBOM STATE, NIGERIA (UNIZIK Journal of STM Education, 2023)
Digital tools in the classroom is nothing new to education. Pioneers in its use in education have much to teach us to enable student acquire knowledge and skills necessary to survive in a digital world. This study investigates digital tools utilization and Chemistry students’ academic achievement in the teaching of soap production in secondary schools. The design was a pretest, posttest quasi-experimental design. The population comprised all the 3840 Chemistry students in the 14 public secondary schools of which 100 students were selected from two intact classes by criterion sampling techniques. Achievement Test on Soap Production (ATSP) was used to collect data with a reliability of 0.78 determined by Kuder Richardson test. Mean and standard deviation were used to answer research questions, while independent T-test was used to test the hypotheses at p≤ .05 level of significance. Findings of the study showed that students taught with digital tools performed better than those taught with expository method. There was a significant difference in their achievement mean scores. But there was no significant difference between male and female students’ achievement mean scores. It was therefore concluded that the utilization of digital tool was effective in teaching soap production. It was recommended that Chemistry teachers should be encouraged to adopt the use of digital tools such as computers in the teaching. Conferences, seminars and workshops should be organized for teachers to acquaint them with latest digital tools to improve the teaching of soap production and other concepts.
Keywords: Digital tools; Utilization; Chemistry; Academic achievement; Soap Production